2008
DOI: 10.1111/j.1574-6968.2007.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of nonylphenol ethoxylates byBacillussp. LY capable of heterotrophic nitrification

Abstract: Biodegradation of nonylphenol ethoxylates (NPEOs) by Bacillus sp. LY, with heterotrophic nitrification ability was investigated. The results showed that NPEOs were readily degraded by Bacillus sp. LY with more than 80% of the total NPEOs being removed within 7 days. Heterotrophic nitrogen removal occurred simultaneously during the biodegradation period of NPEOs. NPEOs were biodegraded through a nonoxidative pathway, through which NPEOs were degraded via sequential removal of ethoxyl units to the nonylphenol. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The 16S rDNA of strain YIC-JL1 has high similarity (>99.5%) with that of many heterotrophic strains in the genus Serratia while that of strain UT10 has high similarity (>99.5%) with that of heterotrophic strain in the genus Bacillus. In previous study, both Serratia and Bacillus with high heterotrophic nitrifying ability were isolated from soil or membrane bioreactor sludge (Kim et al, 2005;Lu et al, 2008Lu et al, , 2014. The successful isolation of heterotrophic nitrifiers from the Yangtze estuarine sediment further confirms the wide engagement of heterotrophic bacteria in the nitrification process in various environments.…”
Section: Isolation Of Heterophic Nitrifiers From Yangtze Estuarine Sementioning
confidence: 58%
“…The 16S rDNA of strain YIC-JL1 has high similarity (>99.5%) with that of many heterotrophic strains in the genus Serratia while that of strain UT10 has high similarity (>99.5%) with that of heterotrophic strain in the genus Bacillus. In previous study, both Serratia and Bacillus with high heterotrophic nitrifying ability were isolated from soil or membrane bioreactor sludge (Kim et al, 2005;Lu et al, 2008Lu et al, , 2014. The successful isolation of heterotrophic nitrifiers from the Yangtze estuarine sediment further confirms the wide engagement of heterotrophic bacteria in the nitrification process in various environments.…”
Section: Isolation Of Heterophic Nitrifiers From Yangtze Estuarine Sementioning
confidence: 58%
“…To date, NPEOs degradation experiments using isolated bacteria only confirmed the formation of low-ethoxylated NPEOs (n=2, 3) (John and White 1998;Lu et al 2008), lowethoxylated NPEOs and NPECs (n=2 or 3) (Liu et al 2006;Sato et al 2001Sato et al , 2003, or NP 1 EO, NP 1 EC, and NP (Liu et al 2007; Fig. 3a).…”
Section: Gammaproteobacteria Betaproteobacteriamentioning
confidence: 91%
“…Bergé et al (2012a) found that total concentrations of NPEO and their metabolites (mainly low-ethoxylated NPEOs and low-ethoxylated NPECs) were 0.10-1,179 μg L −1 (mean, 4.54 μg L ) in surface water. Some biodegradation intermediates, such as NP and low-ethoxylated NPEOs (NP 1-3 EO), exhibit estrogenic properties, and therefore, the biotransformation pathways of NPEOs have been widely studied using isolated bacteria (John and White 1998;Liu et al 2006Liu et al , 2013Lu et al 2008;Sato et al 2001Sato et al , 2003Ying et al 2002). It is generally accepted that at least two EO chain degradation pathways lead to the production of metabolites with shortened ethoxy chains (lowethoxylated NPEOs) and carboxylated ethoxy chains (lowethoxylated NPECs).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, aldehyde was also formed during the reaction of AEO 8 with the NP42a cell extract, which suggests that NP42a can degrade a wide spectrum of compounds with similar structures via the non-oxidative pathway (White et al, 1996;Di Corcia et al, 1998b;Lu et al, 2008).…”
Section: Npeo Biotransformation Pathway Studiesmentioning
confidence: 99%
“…To date, two EO chain-shortening pathways have been elucidated using pure cultures: (i) non-oxidative EO chain (hydroxyl shifts) exo-cleavage with short-chain NPEOs as the main metabolites (n = 2 or 3), which occurs through the release of one molecule of acetaldehyde at each step ( Fig. 1A) (John and White, 1998;Lu et al, 2008) and (ii) EO chain oxidation and exo-cleavage with short chains of NPEOs and NPECs as the main metabolites (n = 2 or 3), which occurs through release of one molecule of glyoxylic acid at each step ( Fig. 1B) (Sato et al, 2001(Sato et al, , 2003Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%